THE ROLE OF THE OMBUDSMAN OF ACEH IN PREVENTING MALADMINISTRATION IN PUBLIC SERVICES: A CASE STUDY OF DP3A ACEH - Ayu, Nadia Pratiwi; Sari, Novita; Ahmady, Iqbal (Universitas Syiah Kuala, 2025)
One of the key institutions overseeing public services in Indonesia is the Ombudsman of the Republic of Indonesia, as outlined in Law Number 37 of 2008 concerning the Ombudsman of the Republic of Indonesia. The Ombudsman has the authority to supervise the implementation of public services provided by State-Owned Enterprises, Regional-Owned Enterprises, State-Owned Legal Entities, as well as private entities or individuals tasked with delivering public services that are partially or fully funded by the national or regional budgets. This research aims to analyze the role of the Ombudsman of Aceh in preventing maladministration and to examine their efforts related to public service issues within the Department of Women Empowerment and Child Protection (DP3A) Aceh. Employing a qualitative, descriptive approach, the study collects primary data through in-depth interviews with various stakeholders and supplements this with secondary data obtained from document analysis, including Law Number 37 of 2008, relevant regulations, and media reports. The findings highlight the significant role and proactive efforts of the Ombudsman of Aceh in addressing alleged maladministration within DP3A Aceh, functioning as an external supervisory body. Their efforts encompass a range of actions that demonstrate responsiveness and a commitment to fostering good governance. In addition to providing recommendations, the Ombudsman actively monitors the implementation of corrective measures to ensure compliance. In conclusion, the study reveals instances of maladministration within UPTD-PPA Aceh, particularly procedural deviations in handling Domestic Violence (KDRT) complaints involving children. The Ombudsman of Aceh identified these issues in accordance with the provisions of Law Number 25 of 2009 concerning Public Services.